2011
DOI: 10.1155/2011/284050
|View full text |Cite
|
Sign up to set email alerts
|

A Program of Nutritional Education in Schools Reduced the Prevalence of Iron Deficiency in Students

Abstract: The objective was to determine the prevalence of iron, folates and retinol deficiencies in school children and to evaluate the changes after an intervention of nutritional education. The project was developed in 17 schools. The sample included 1,301 children (678 males and 623 females). A subsample of 480 individuals, was randomly selected for drawing blood for biochemical determinations before and after the intervention of nutritional education, which included in each school: written pre and post-intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 10 publications
2
12
0
3
Order By: Relevance
“…Children who consumed dark green leafy vegetables and legumes had higher ferritin values than those who did not consume these foods (p<0.05). In a study investigating a program of nutritional education in schools aimed at reducing the prevalence of iron deficiency anemia in Venezuela, it was found that iron deficiency prevalence was higher among children who consumed less fruits and dark green leafy vegetables [20]. The reason is that dark green leafy vegetables and legumes (beans) are good sources of iron, and the consumption of these foods ensures improved iron nutritional status [18].…”
Section: Discussionmentioning
confidence: 99%
“…Children who consumed dark green leafy vegetables and legumes had higher ferritin values than those who did not consume these foods (p<0.05). In a study investigating a program of nutritional education in schools aimed at reducing the prevalence of iron deficiency anemia in Venezuela, it was found that iron deficiency prevalence was higher among children who consumed less fruits and dark green leafy vegetables [20]. The reason is that dark green leafy vegetables and legumes (beans) are good sources of iron, and the consumption of these foods ensures improved iron nutritional status [18].…”
Section: Discussionmentioning
confidence: 99%
“…Children are more vulnerable to developing anaemia because they are rapidly growing and liable to infection. Moreover, micronutrients such as iron and folic acid are likely to be inadequate in children's diets if parents are not well informed [2,9,10,11]. Anaemia is not only one of the leading causes of childhood mortality and morbidity [12], it may also affect cognitive development and school performance [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore undertook this epidemiological study to determine the prevalence of anaemia, and some of its determinants, in an area in the north of Sudan. This would help local health decision-makers to plan for prevention and comprehensive management of this important health problem [2,3,11].…”
Section: Introductionmentioning
confidence: 99%
“…Hasil penelitian Zulaikah memberikan simpulan bahwa intervensi pendidikan gizi secara komprehensif pada anak, orang tua/ wali, dan guru kelas berperan terhadap peningkatan kadar hemoglobin anak (10). Penelitian lain mengungkapkan bahwa Model Triangulasi Informasi, yaitu pendidikan gizi yang diberikan kepada guru, orangtua, dan siswa dapat merubah perilaku hidup sehat (11).…”
Section: Pendahuluanunclassified